The Steel Industry in Global Competition and Limited Capital: A Case Study of the Steel Industry in Bolivia - Antonio Rafael da Riga (Global Writing Academica Researching and Publishing, 2023)
This article has as its objective to present a study of the impact of tax costs of the investment destined to the expansion of a metallurgical plant in Bolivia, compared with the tax load that would occur if such the investment were made in other countries, specifically, the USA, Canada and Chile. The study has been developed within the context of recognition that certain events which provoke effects upon the level of competitiveness of companies are beyond their action range. Among such events, the tax load, an integral element of government macroeconomic policies, has been considered in this study. The multiple case study method was used to measure the tax cost of a planned investment, contemplating the effective legislation in each of the examined countries. Results of the study allow concluding that, among the four countries under analysis, Brazil presents the largest tax cost, significantly greater than the other countries, which offer fiscal incentives, including a negative tax load. Among the remaining three countries, the company competitiveness has been favoured according to the following order: by Chile, the USA and Canada.